Benefits of the Principles of Perry Neighborhood Unit through Supply Chain Strategy in Nong Chik Heights, Johor Bahru, Malaysia - Jumadil Saputra; Rahaya Md. Jamin; Siti Aisyah Saat; Rozita Muhamad Nawi; Mohd Najib Ramli (International Journal of Supply Chain Management, 2019)
This study attempts to investigate the combination of new towns concept goal of honeycomb concepts integrated through the application of the supply chain strategy in Perry Neighborhood Unit Principles founded on